2008
DOI: 10.3727/000000008783906982
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell Research: Current Situation and Problems

Abstract: The concept of a "cancer stem cell system" that continues to supply cancer component cells has been proposed. It is time to apply stem cell studies, which is a field of expertise in regenerative medicine, to cancer treatment. Cancer treatments that effectively attack cancer stem cells acting as a manufacturing plant for producing differentiated cancer progenies will be designed by revealing the cancer stem cell system. Therefore, in the near future we hope that revolution will occur in cancer therapy to eradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, it has been demonstrated that they be isolated by several ways including surface marker sorting (Al-Hajj et al, 2003;Singh et al, 2004), side-population cells selecting (Hadnagy et al, 2006;Moserle et al, 2010), and mammosphere cultures (Ponti et al, 2005;Yu et al, 2008). Most CSCs form clones when nurtured in low adhesive vessels (Chumsri and Burger, 2008;Kobayashi et al, 2008;Gilbert and Ross, 2009), and further generate sphere clones in the present of growth factors such as epidermal growth factor (EGF). Therefore the sphere clone formation assay has been widely used for the separation and identification of CSCs (Ponti et al, 2005;Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that they be isolated by several ways including surface marker sorting (Al-Hajj et al, 2003;Singh et al, 2004), side-population cells selecting (Hadnagy et al, 2006;Moserle et al, 2010), and mammosphere cultures (Ponti et al, 2005;Yu et al, 2008). Most CSCs form clones when nurtured in low adhesive vessels (Chumsri and Burger, 2008;Kobayashi et al, 2008;Gilbert and Ross, 2009), and further generate sphere clones in the present of growth factors such as epidermal growth factor (EGF). Therefore the sphere clone formation assay has been widely used for the separation and identification of CSCs (Ponti et al, 2005;Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…injection or subcutaneous admin istration of a specific number of stem cells directly into therapeutically targeted areas. In addition, the high plasticity and migratory potential of BM stem cells also offer the possibility of mobilizing them in vivo or injecting these stem cell types in circulation to regenerate the particular functional progenitors for the tissue regeneration [15] [13]. However, molecular targeting of tumori genic cascade elements in tissue specific cancer progenitor cells, which are derived from the malig nant transformation of adult stem cells, also repre sents a novel approach for the treatment of diverse metastatic and incurable cancer types by combina tion therapies [14].…”
Section: Stem Cell Based Therapymentioning
confidence: 99%
“…Since the metastatic spread of diverse tumor cells, including those from glioblastomas, melano mas, and pancreas, breast, and prostate cancers to other specific tissues/organs, such as lymph nodes, bone, lungs, and/or liver, appears to be governed by the expression of diverse angiogenic factors, such as VEGF VEGFR system, matrix metallo proteinases, urokinase type plasminogen activator (uPA), cyclooxygenase 2 (COX 2), chemokines, and surface adhesion molecules, their molecular targeting may also constitute another adjuvant can cer therapy [15]. In this matter, the specific block ade of the SDF 1 CXCR4 axis by using a specific anti SDF 1 antibody, anti CXCR4 antibody, or CXCR4 antagonist (TC14012, TN14003, or AMD3100) has notably been observed to prevent the metastatic spread and interfere with the hom ing of breast and prostate cancer epithelial cells at their target metastatic sites, including lymph nodes, bone, and lungs [16].…”
Section: Growth Factor Signaling Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations